Characterizing the agroecological transition of Italian farming systems using FADN database - Sarah Stempfle; Simone Russo; Vincenzo Fiore; Ruggiero Sardaro; Piermichele La Sala; Luigi Roselli (Environmental and Sustainability Indicators)
The Common Agricultural Policy 2023–2027 encourages the transition towards sustainable agriculture in line with the goals of the European Green Deal. Agroecology is gaining recognition as a valuable approach to enhance the sustainability of faming systems. However, there is limited understanding of the status quo of the farming systems and their readiness for transition, especially at large scales such as the national one. This paper investigates the current uptake of agroecology across the Italian farming systems, by adapting the Tool for Agroecology Performance Evaluation (TAPE) methodology to use secondary data from the Farm Accountancy Data Network (FADN). Besides, a panel between-variance regression was estimated to identify the key determinants of the transition degree. The results indicate that agroecology has not yet been widely adopted by the Italian farms. Additionally, factors such as the type of farming, farm management, farm economic and physical size, farm location, and farmer's socio-demographics play a significant role in explaining the variation in the transition intensity towards an agroecological production system. The findings provide a knowledgebase for developing targeted policies and monitoring progress in agroecological transition. The study confirms the viability of using the FADN to evaluate the degree of agroecological transition, while also revealing information gaps. Although essential environmental and social information will be included in the forthcoming Farm Sustainability Data Network, further integrative sources should be explored to capture multifaced aspects of agroecological transition within broader agri-food systems, while in-depth studies based on primary data collection could offer more detailed and nuanced insights.